Home spirometry in bronchiolitis obliterans after allogeneic haematopoietic cell transplant. Issue 1 (19th July 2018) - Loiseau, Clémence; Lemonnier, François; Randrianarivelo, Odile; Itzykson, Raphael; Nguyen, Stéphanie; Becquemin, Marie Hélène; Tcherakian, Colas; Uzunov, Madalina; Catherinot, Emilie; Rivaud, Elisabeth; Salvator, Hélène; Devillier, Philippe; et al.
Bronchiolitis obliterans syndrome (BOS) is a well-characterised late-onset noninfectious pulmonary complication of allogeneic haematopoietic stem cell transplantation (HSCT), occurring in 2% to 26% of recipients [1]. It is considered to be a pulmonary manifestation of graft versus host disease (GVHD) [2] and is associated with a mortality rate varying from 14% to 100% in historical series [3, 4]. Although immunosuppressive drugs are modestly effective, early diagnosis and treatment could improve its outcome [5]. After lung transplantation, home spirometry monitoring of pulmonary function allows early detection of BOS [6]; it is associated with a better response to steroids [7] and consequently is considered as a standard of care [8]. Our group was the first to report the use of home spirometry in 37 HSCT recipients [9]. More recently, Cheng et al . [10] showed a good correlation between home spirometry and classical laboratory spirometry in this population. We present here the incidence and long-term outcome of BOS occurring after HSCT in an extended cohort of 110 patients monitored with home spirometry. Long-term outcome of patients with BOS after HSCT with home spirometry is encouraging despite suboptimal adherence http://ow.ly/mKfM30jDknz